2020
DOI: 10.1007/s00701-020-04290-0
|View full text |Cite
|
Sign up to set email alerts
|

The membrane of Liliequist—a safe haven in the middle of the brain. A narrative review

Abstract: Background The membrane of Liliequist is one of the best-known inner arachnoid membranes and an essential intraoperative landmark when approaching the interpeduncular cistern but also an obstacle in the growth of lesions in the sellar and parasellar regions. The limits and exact anatomical description of this membrane are still unclear, as it blends into surrounding structures and joins other arachnoid membranes. Methods We performed a systematic narrative review by searching for articles describing the anatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Beneath the third ventricle lies the membrane of Liliequist. This partially trabecular and partially dense structure presents a projection of the arachnoid membrane [ 14 ]. It consists of three segments, which separate the chiasmatic, interpeduncular and prepontine cisterns [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beneath the third ventricle lies the membrane of Liliequist. This partially trabecular and partially dense structure presents a projection of the arachnoid membrane [ 14 ]. It consists of three segments, which separate the chiasmatic, interpeduncular and prepontine cisterns [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity both in the superficial subarachnoid and basal cisterns seems to be the rule in all anatomical studies. Some of the variations arise from the expected variability during embryogenesis, others from the type of study conducted and method being used 35. The volumes of trabeculae differ between subjects and locations.…”
Section: Discussionmentioning
confidence: 99%
“…[2,8] Neurosurgical studies have described physiological perforations in Liliequist membrane. [9] Cases of spontaneous third ventriculostomy have been reported in patients of chronic hydrocephalus. [10] Cavalheiro et al in 2021 reported spontaneous third ventriculostomy in three cases of myelomeningocele and were able to demonstrate flow void across the site of Liliequist membrane on MRI in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosurgical studies have described physiological perforations in Liliequist membrane. [ 9 ] Cases of spontaneous third ventriculostomy have been reported in patients of chronic hydrocephalus. [ 10 ] Cavalheiro et al .…”
Section: Discussionmentioning
confidence: 99%